The role of Rapid Intraoperative Parathyroid Hormone (ioPTH) assay in determining outcome of parathyroidectomy in primary hyperparathyroidism: A systematic review and meta-analysis. (August 2021) - Medas, Fabio; Cappellacci, Federico; Canu, Gian Luigi; Noordzij, Jacob Pieter; Erdas, Enrico; Calò, Pietro Giorgio
Abstract: Background: Primary hyperparathyroidism (PHPT) is a common endocrine disorder. In the last few decades, the introduction of Rapid Intraoperative Parathyroid Hormone (ioPTH) monitoring has allowed to ensurance of the excision of all hyperfunctioning parathyroid tissues, reducing the risks of persistent and recurrent PHPT. However, the use of ioPTH is still debated among endocrine surgeons. Material and methods: The objective of this systematic review and meta-analysis was to assess if ioPTH monitoring is able to reduce the incidence of persistent or recurrent PHPT. A systematic literature search was performed using PubMed, Scopus, ISI-Web of Science and Cochrane Library Database. Prospective and retrospective studies addressing the efficacy of ioPTH monitoring were included in the systematic review and meta-analysis. The random-effects model was assumed to account for different sources of variation among studies. The overall effect size was computed through the inverse variance method. Heterogeneity across studies, possible outlier studies, and publication bias were evaluated. Results: A total of 28 studies with 13, 323 patients were included in the quantitative analysis. The incidence of operative failure was 3.2% in the case group and 5.8% in the control group. After excluding three outlier studies, the quantitative analysis revealed that ioPTH reduced significantly the incidence of postoperative persistent or recurrent PHPT. (Risk Difference = −0.02; CI = −0.03, −0.01; p < 0.001). There was no evidence of heterogeneity among the studies (Q = 19.92, p = 0.70; I 2 = 0%). The analysis of several continuous moderators revealed that the effectiveness of ioPTH was larger in studies with lower preoperative serum calcium values and higher incidences of multiple gland disease. Conclusion: ioPTH monitoring is effective in reducing the incidence of persistent and recurrent PHPT. Its routine use should be suggested in the next guidelines regarding management of PHPT. Graphical abstract: Image 1 Highlights: Primary hyperparathyroidism is a common endocrine disorder, surgery is the only definitive treatment. The main causes of postoperative persistent disease are multiple gland disease and ectopic gland localisation. The use of intraoperative PTH assay significantly reduces postoperative failures and should be considered for routine use.